PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SMART TBK PADANG HALABAN - Zebua, Yuniman (Universitas Labuhanbatu, 2021)
This study aims to determine the effect of leadership, work environment, work motivation, and job satisfaction on employee performance at PT. SMART Tbk Padang Halaban. This type of research is associative research. Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 50 respondents, while the population used in this study was at PT. SMART Tbk Padang Halaban. The data collection technique is done by interview, questionnaire, and documentation study. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The data analysis technique in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t-test), simultaneous significance testing (F test), and determination coefficient testing (R2). The results of this study indicate partially (t test) it is known that leadership has a significant effect on employee performance at PT. SMART Tbk Padang Halaban. Work Environment has a significant effect on Employee Performance at PT. SMART Tbk Padang Halaban. Work Motivation has a significant effect on Employee Performance at PT. SMART Tbk Padang Halaban. Then Job Satisfaction has a significant effect on Employee Performance at PT. SMART Tbk Padang Halaban. In simultaneous testing (F test) it is known that leadership, work environment, work motivation, and job satisfaction have a significant effect on employee performance at PT. SMART Tbk Padang Halaban. Through testing the coefficient of determination (R Square) 58.6% means that Leadership, Work Environment, Work Motivation, and Job Satisfaction have a significant effect on Employee Performance by 3.43%, the remaining 2.85% is influenced by other variables not examined in this study.